Anion templated self-assembly - From anion complexes to the formation of supramolecular 2D networks - ALETTI, ANNA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
This thesis, entitled “Anion Templated Self-Assembly – From Anion Complexes to the Formation of Supramolecular 2D Networks” covers the anion complexation and ATSA abilities of different sets of ligands. The work will be divided into five chapters, gathering the work on each different sets of ligands separately. Chapter 1 will introduce the most recent advances in anion complexation and aniontemplated self-assembly, from the formation of 1:1 (Ligand:Anion) complexes to the formation of higher order bundles. Particular focus will be given to the use hydrogen bonding as the main interaction for the formation of anion-templated self-assemblies. Chapter 2, will discuss the synthesis and anion binding studies of tripodal tris(urea) ligands with Cl - , CH 3 COO - , H 2 PO 4 - and SO 4 2- . The anion binding studies carried out in solution on these ligands indicated that ATSA was occurring which lead us to investigate also the self-assembly behaviour in solution and in the solid state, which will also be discussed in detail. Chapter 3 will focus on the synthetic challenges engaged to obtain ‘dipodal’ ligand, not simply as a side product. Solution binding studies on a dipodal thiourea analogue with 4 tetrahedral anions (i.e. H 2 PO and SO 4 2- ) will be included in this chapter. In chapter 4 the formation of anionic complexes with a family of macrocycles and [2]catenanes, combining the 2,6-bis(triazolo)pyridine (BTP) moiety and amide groups as binding units, will be presented. The discussion will cover the differences given by the different substitution pattern and the higher preorganisation of hydrogen bond donors within the [2]catenanes structures. Chapter 5 will include the studies on halide encapsulation within bis(tren) cage with imidazolate binding units, which were carried out in collaboration with Prof. Amendola, from Università degli studi di Pavia. Detailed NMR characterisation of the anionic complexes will be presented, which will show the conformational changes caused by the encapsulation of the halide anions. Chapter 6 will provide detailed experimental procedures. References are provided in Chapter 7 and supplementary data and spectra are presented in the Appendices A2-A5.
APPROVED
Keywords: Anion; Supramolecular Chemistry; Self-Assembly; Anion-Template